Coaching efficacy, player perceptions of coaches' leadership styles, and team performance in premier league soccer - Keatlholetswe, L.; Malete, L. (Research Quarterly for Exercise and Sport, 2019)
The coaching competency research has demonstrated the role of coaching efficacy and coaching behaviors on various athlete outcomes. However, athlete perceptions of these relationships and how they affect performance are less understood. Purpose: This study examined if coaching efficacy is predictive of player perceptions of coaches' leadership styles, team atmosphere, and team performance in a soccer season. Method: Fifteen male premier league soccer coaches (Mage = 45.27, SD = 6.07) and 226 players (Mage = 25.66, SD = 3.96) from Botswana participated in the study. All participants completed a background information questionnaire. Coaches completed the Coaching Efficacy Scale. Players rated their coaches' leadership styles using the Revised Leadership Scale for Sports as well as team atmosphere. Team performance was based on position in the league log and player ratings of the teams' performance. Results: Findings showed that coaches' self-ratings on technique efficacy predicted player perceptions of the coaches' use of all six leadership styles. Game strategy efficacy predicted higher team atmosphere and team performance. Motivation efficacy was not significantly associated with player perceptions of the coaches' use of any of the leadership styles, while character building efficacy was negatively associated with the various leadership styles. Conclusion: Findings provide support to previous research evidence linking higher coaching efficacy, leadership styles, and team outcomes. The study expands the emergent research within the coaching competency literature that examines player perceptions of coaches' behaviors and leadership styles.